THE INFLUENCE OF WORK MOTIVATION AND TRAINING ON SALES PERFORMANCE AT PT. ORIENTAL STARS FIELD - Fitri Ramadhani; Prihatin Lumbanraja; Iskandarini (CV. Radja Publika, 2024)
Medan Oriental Stars opens job vacancies for Putra/I North Sumatra working in the field of sales marketing via social media. The results show that in January there were 150 Sales people legally accepted as employees at PT. Oriental Stars Field. This month the company has a sales target of 10 cars sold. In the first month the sales level did not reach the target set by the company. In February to September the target level for car unit sales from PT. Medan Oriental Stars Chery rose several percent from the previous target and the results were very unsatisfactory for the company. This research aims to determine and analyze the influence of work motivation and training on sales performance at PT. oriental star field. The population in this research is sales of PT. Medan Oriental Stars, namely 120 respondents. If rounded up, the number of samples taken in this research is 92 samples. The sampling technique used is simple random sampling. The data analysis method uses multiple linear regression analysis. The research results show that motivation has a positive and significant effect on sales performance. Training has a positive and significant effect on sales performance. Motivation and training have a positive and significant effect on sales performance.